HUBUNGAN STATUS MEROKOK TERHADAP KUALITAS TIDUR PADA REMAJA TINGKAT SLTA DI KECAMATAN BONJOL DAN LUBUK SIKAPING - Abdi, Tri Jaya; Anggrainy, Fenty; Susanti, Restu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Smoking is the biggest health problem faced. This activity has at least had a negative impact such as a decrease in sleep quality due the release of cathecholamines resulting in tachycardia and increase in blood preasure which increases alertness.Objective: This study aims to determine the characteristic, smoking status, and the relationship of smoking with the sleep quality of adolescent at the senior high school level. Methods: This type of research is a descriptive analytic study with a cross-sectional study design with convenience sampling technique. The population of this study was school-age students at the high school level in the districts of Bonjol and Lubuk Sikaping with a total sample of 96 people. Data obtained in the form of primary data from Pittsburgh Sleep Quality Index (PSQI) questionnaire Results: The highest group of school-aged adolescents were boys aged 17 and 18 years, with the most categories being smokers and poor sleep quality. Regarding the relationship between smoking status, there was a statistically significant relationship with sleep quality. This study also found that adolescents with smoking status were 5,402 times more likely than smokers (ex-smokers and non-smokers) to decrease sleep quality (p=0.001;OR=5.402) Conclusion: There is a significant relationship between smoking status and sleep quality.